Choral singing in the early years of elementary school - Pavlović, Biljana M.; Cicović Sarajlić, Dragana J.; Kovač, Anđelka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper discusses choral singing as a form of extracurricular activity and teaching in elementary school. It considers the historical development of choral singing in order to highlight the continuity of its existence and importance in society and reviews the importance of choral singing in musical and overall upbringing and education of elementary school students. Authors analyze the curricula of grades I to IV in order to determine how much attention is given to choral singing. Didactic and methodological issues related to the formation of the choir in elementary school are reviewed, together with methodical approach for working with early grades choir, proper selection of the musical compositions and the role of teachers. Listed is the recommended choral literature to supplement the current curricula. Special attention was given to literature containing the Kosovo-Metohija folk songs, suitable for choral arrangement. Performing of these songs in a choral arrangement will contribute to stimulating the interest of students towards musical folklore of Kosovo and Metohija, and therefore its preservation and fostering. It is highlighted that singing in the choir contributes to the development of hearing, voice, harmonic feeling, a sense of rhythm, melody and group play. By mastering different compositions, students become familiar with valuable achievements of artist, spiritual and folk music. The significant meaning and importance of this kind of work is reflected in the possibilities of achieving the tasks of socio-moral education. Choral singing develops a sense of collective responsibility, conscious discipline, perseverance, endurance, helps establish a sense of understanding, mutual respect and tolerance, friendship and a sense of teamwork. Singing in the choir develops aesthetic attitude and taste in music. Students are trained to perceive and to value the true qualities of beauty, grace, harmony and authenticity in music. The value of this kind of work is also reflected in the capabilities of the development of work habits, work culture and discipline. Choral singing encourages emotional and psychological development of students. Group singing relaxes students, reduces stage fright and uncertainty, and promotes self-esteem. Singing variety of lyrics enables students to acquire knowledge, and form a more positive attitude towards life. Choral singing contributes to the development of skills and good habits, motivation of students to learn, self-education, self-development, encourages the development of attention, memory, concentration, thinking, contributing to the achievement of the goals of intellectual education. In addition to the educational influence on the members of the choir, it enriches also the listeners and contributes to their musical and cultural development, as well as the reputation and recognition of the school. It was concluded that the choir, as the largest form of collective music performance in elementary school, has an extremely important role in the musical and the comprehensive development of students, which is why it should receive much more attention in the context of elementary school extracurricular activities.